Chapter The impact of technological change on medieval fashion - Wilson, Laurel (Datini Studies in Economic History, 2022)
In the early fourteenth century, a new fashion system appeared in Europe, one which was based on constant change and the privileging of the new. This paper argues that the new system did not appear simply as a response to consumer demand; it was also precipitated in part by two major technological innovations: the thirteenth-century development of the advanced broadloom, and the new tailoring techniques of the early fourteenth century. These technological innovations thus helped to precipitate the fashion revolution in obvious material ways, but they also led less directly to social and economic changes which were equally important to the development of fashion.